LINGUACULTURAL ANALYSIS OF HUMOR IN SOCIAL MEDIA: EXPLORING THE INTERSECTION OF LANGUAGE, CULTURE, AND DIGITAL COMMUNICATION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Humor on social media platforms has emerged as a primary form of digital communication, transcending geographical, cultural, and linguistic barriers. This paper presents a linguacultural analysis of humor in online spaces, investigating how language and culture interact to produce humorous content. By analyzing memes, viral videos, and other comedic forms circulating on platforms such as Twitter, Instagram, TikTok, and Facebook, this study explores the linguistic mechanisms employed in humor production, as well as the cultural dimensions influencing the interpretation of jokes. Through this analysis, the paper highlights the impact of social media in shaping modern humor, reflecting societal values, and fostering cross-cultural communication. Ultimately, humor on social media is found to be a dynamic, multilayered phenomenon, with significant implications for identity formation, community building, and the negotiation of cultural norms in digital spaces.